Effect of Cold Storage on the Quality of Epididymal Semen of Slaughterhouse Derived Buck Testes - Singh, Hari Om; Singh, Bhoopendra; Kumar, Rajesh; Srivastava, Sushant; Singh, Jitendra P. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was carried out on 48 pairs of testicles from mature bucks, irrespective of breed, slaughtered at local abattoirs of Faizabad and Sultanpur districts, UP and at AL-Nafees Protein Pvt. Ltd., Mewat, Haryana. The testicles were collected and stored in plastic bags in ice chest at 4°C and immediately transferred to the laboratory. The testicles were randomly divided into six storage groups, i.e., 6, 12, 24, 48, 72 and 96 hours; eight pairs of testicles in each group. After completion of storage time, testes of respective storage groups were cleaned with physiological saline solution, and the fascia, blood vessels, and sheath were removed using BP blade and thumb forceps. The various epididymal seminal attributes assessed were semen volume, sperm concentration, total sperm recovery, sperm motility, viability, abnormality, and HOS reactivity using standard procedures. The volume of epididymal semen harvested differed significantly with storage time. The sperm concentration did not vary significantly up to 48 hours of storage; sperm motility and viability did not differ significantly up to 12 hours of cold storage, while there was a progressive increase in abnormality and decrease in HOS reactivity. Thus, cold storage preservation and harvesting of epididymal semen up to 48 hours can be made to conserve the fertility of precious dead/slaughtered buck.